Perinatal iron deficiency alters the cardiac proteome and mitochondrial function in neonatal offspring - Holody, Claudia D; Woodman, Andrew G; Nie, Chunpeng; Liu, Si Ning; Young, Daniel; Wiedemeyer, Alyssa; Carpenter, Rowan; Noble, Ronan M N; Graf, Daniel; Dufour, Antoine; Lemieux, Hélène; Bourque, Stephane L (American journal of physiology. Heart and circulatory physiology, 2025)
Iron deficiency (ID) is common during gestation and early infancy and can alter developmental trajectories with lasting consequences on cardiovascular health. Iron plays a critical role in systemic oxygen transport (via hemoglobin) and aerobic respiration (as a component of mitochondrial complexes). Perinatal ID has been shown to cause cardiac dysfunction in neonates, but the mechanisms underlying these changes have not been characterized. Here, we examined the effects of perinatal ID on cardiac mitochondrial function in rats in the early postnatal period. Female rats were fed an iron-restricted or iron-replete diet before and during pregnancy. Offspring hearts were collected postmortem for quantitative shotgun proteomic analysis [postnatal days (PD) 0 and 28] and mitochondrial function was assessed by high-resolution respirometry (at PD 0, 14, and 28). Markers of oxidative stress were measured by fluorescence microscopy and assessment of antioxidant gene expression profiles. Both male and female ID pups had reduced body weight and increased relative heart weights at all time points assessed, despite recovering from anemia by PD28. Proteomics analysis revealed dysregulation of mitochondrial proteins by ID, and these differences were most pronounced in males. In male hearts, ID increased mitochondrial content and decreased normalized mitochondrial respiration through the NADH-pathway, succinate-pathway, and fatty acid oxidation (FAO)-pathway. In conclusion, ID causes changes in cardiac mitochondrial function in neonates, which may reflect inadequate or maladaptive compensation during the transition from intrauterine to extrauterine life. Furthermore, the results presented herein, which were stratified by offspring sex, underscore the need for follow-up studies to directly assess differences in how male and female offspring cope with ID as a perinatal stressor. Iron deficiency (ID) is the most common nutritional deficiency worldwide and is highly prevalent among pregnant women and young children. ID causes changes in mitochondrial protein expression and function in neonatal hearts, which may contribute to functional impairments. Improving cardiac energy metabolism may represent a novel approach to improve short- and long-term outcomes in infants affected by ID, but sex of the neonate may be an important determinant of treatment efficacy.